2019
DOI: 10.3386/w26128
|View full text |Cite
|
Sign up to set email alerts
|

Tax-Sheltered Retirement Accounts: Can Financial Education Improve Decisions?

Abstract: We conduct a stated-choice experiment to analyze the decision to contribute to front-or back-loaded tax-sheltered savings accounts. Our experimental design includes a randomized financial education treatment that provides information on the two types of accounts. We assess whether respondents learn about the tax implications of these accounts, and whether they make better contribution choices when exposed to the financial education intervention. We find that, relative to a control group, our intervention impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The aims of incentivizing better planning of retirement savings and raising greater interest in individual plans were achieved, as attitudes improved and contributions increased by 40%. Boyer et al (2019), in line with Collins and Urban (2016), deepened the topic of retirement savings by studying a sample of 3000 Canadians aged between 35 and 55. However, the authors did not focus on how much individuals should save for retirement, but focused on how much their decisions are productive in terms of risk–return ratio.…”
Section: Related Literaturementioning
confidence: 99%
“…The aims of incentivizing better planning of retirement savings and raising greater interest in individual plans were achieved, as attitudes improved and contributions increased by 40%. Boyer et al (2019), in line with Collins and Urban (2016), deepened the topic of retirement savings by studying a sample of 3000 Canadians aged between 35 and 55. However, the authors did not focus on how much individuals should save for retirement, but focused on how much their decisions are productive in terms of risk–return ratio.…”
Section: Related Literaturementioning
confidence: 99%
“…Financial education is a commonly used method to promote or facilitate retirement savings (e.g., Atkinson et al, 2015;Boyer et al, 2019). Individual and systematic studies on interventions that only offer financial education or advice to promote retirement savings thus far have demonstrated mixed financial outcomes.…”
Section: Financial Outcomes Of Interventionsmentioning
confidence: 99%
“…Indeed, Clark et al (2006) claimed that, after participating in financial education seminars, individuals are more likely to change investment allocations and start new tax deferred saving accounts. Along this line, Boyer et al (2019) pointed out the importance of filling the knowledge gap of tax-sheltered retirement instruments in Canada. In a randomized experiment, the authors proposed a survey through which they showed a significant improvement both in the knowledge about tax-favored saving vehicles and in the quality of the decisions made.…”
Section: Savings Trajectoriesmentioning
confidence: 99%